Limited-damage 3D-printed interlocking connection for timber volumetric structures: Experimental validation and computational modelling. (1st January 2023) - Li, Zhengyao; Tsavdaridis, Konstantinos Daniel
Abstract: Cross laminated timber volumetric construction (CLTVC) is an innovative construction technology that combines the sustainability of timber and the efficiency of modular construction, as opposed to conventional construction. However, the connection installing methods of CLTVC, such as fastening, are laborious with limited accessibility for connection installations, thus hindering the application of CLTVC in mid- and high-rise structures. Therefore, a new way of connecting CLT modules by sliding and stacking is explored herein with a newly proposed damage-control interlocking connection system, aiming to provide a more efficient assembly solution to CLTVC that does not require onsite screwing. Quasi-static monotonic and cyclic test, and numerical analyses were conducted to assess the mechanical performance of the proposed connections, which possessed adequate translational stiffness and strength of the proposed connections. The connections' ability to control deformation, while damage is moved away from timber and the embedded fasteners, was also well demonstrated in the test, as both screws and timber remained mostly intact after testing. This novel connection design showcases a new concept of modules' assembly in volumetric construction with higher efficiency and flexibility; meanwhile demonstrates the potential in reducing the permanent damage to structural materials during service life and enabling reuse. Highlights: Detailed review of connection systems for Cross Laminated Timber volumetric structures. Development of an interlocking connection system for CLT volumetric structures. Finite element analyses on the translational behaviours of the proposed connection system. Monotonic and cyclic testing on 3D printed specimens demonstrates damage-control capacity of the proposed design.